Enhancement Network Monitoring System Functionality by Implementing an Android-based Notification System to Monitor Virtual Servers on Cloud Computing Network - Christanto, Febrian Wahyu; Sani Suprayogi, Mohammad (IJAIT (International Journal of Applied Information Technology), 2018)
Computer networks have evolved with the presence of cloud computing technology to accommodate the problem of inadequate computer devices and application services that are not integrated. USM (Universitas Semarang) which located in Indonesia is an educational institution that has implemented cloud computing technology using ROCCA (Roadmap for Cloud Computing Adoption) to accommodate the needs of internal application systems at this institution. The problem arises because the system administrator of the computer network is difficult to monitor the condition of the virtual server running because physically, the virtual server cannot be seen and touched. If there is a problem in one service, then the repair process takes a long time because there is not enough notification system to provide fast and detailed information about the condition of the virtual server running so that it will interfere with the quality of service from internal application system. The solution of these problems enhances the NMS (Network Monitoring System) functionality with notification system technology. Use PPDIOO method, this research will combine Pandora FMS and Telegram based on Android platform to implement a fast notification system in monitoring conditions virtual server resources which directly sent the message to the system administrator’s smartphone. The expectation of this research is the quality of internal application service at USM (Universitas Semarang) can be properly maintained.